Global research trends in in-stent neoatherosclerosis: A CiteSpace-based visual analysis - Wang, Heng; Wang, Qian; Hu, Jie; Zhang, Ruijing; Gao, Tingting; Rong, Shuling; Dong, Honglin (Frontiers in Cardiovascular Medicine, 2022)
Background Recent studies have shown that in-stent neoatherosclerosis (ISNA/NA) is an important cause of late stent failure. A comprehensive understanding of the current state of research in this field will facilitate the analysis of its development trends and hot frontiers. However, no bibliometric correlation has been reported yet. Here, we analyze the relevant literature since the emergence of the concept and provide valuable insights. Methods Publications were collected from the Web of Science Core Collection (WoSCC) and PubMed. Microsoft Excel, SPSS and CiteSpace were used to analyze and present the data. Results A total of 498 articles were collected, with Japan and Cardiovasc Res Fdn being the main publishing forces in all country/region and institutions. J AM COLL CARDIOL is the journal with the most published and co-cited articles. According to co-citation analysis, optical coherence tomography, thrombosis, implantation, restenosis, drug-eluting stent, and bare metal stent have become more and more popular recently. Conclusion ISNA is a niche and emerging field. How to reduce the incidence of ISNA and improve the late patency rate of coronary stents may remain a hot spot for future research. The pathogenesis of ISNA also needs to be explored in more depth.